2008
DOI: 10.1098/rspb.2008.1193
|View full text |Cite
|
Sign up to set email alerts
|

Indirect genetic effects and the evolution of aggression in a vertebrate system

Abstract: Aggressive behaviours are necessarily expressed in a social context, such that individuals may be influenced by the phenotypes, and potentially the genotypes, of their social partners. Consequently, it has been hypothesized that indirect genetic effects (IGEs) arising from the social environment will provide a major source of heritable variation on which selection can act. However, there has been little empirical scrutiny of this to date. Here we test this hypothesis in an experimental population of deer mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
160
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 56 publications
3
160
1
1
Order By: Relevance
“…Indeed, Saltz [13] reported that the overall aggressiveness of a group of male D. melanogaster is influenced by the genetic composition of that group, or rather, by indirect genetic effects (IGEs). Further evidence for IGEs is provided by Kent et al [46], who report that chemical signalling employed by this species also varies based on the genotypes of neighbours; similar effects of genetic social environment have been documented in mice [47]. Therefore, if genetically determined aggression levels vary within our population, it is possible that social heterogeneity, rather than kinship, may be responsible for the between-treatment variation seen in overall group aggression.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, Saltz [13] reported that the overall aggressiveness of a group of male D. melanogaster is influenced by the genetic composition of that group, or rather, by indirect genetic effects (IGEs). Further evidence for IGEs is provided by Kent et al [46], who report that chemical signalling employed by this species also varies based on the genotypes of neighbours; similar effects of genetic social environment have been documented in mice [47]. Therefore, if genetically determined aggression levels vary within our population, it is possible that social heterogeneity, rather than kinship, may be responsible for the between-treatment variation seen in overall group aggression.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the behaviour-predictability feedback is predicted to promote consistency (via a form of correlational selection that favours individuals continuing to do what they have done in the past) in leader-follower situations [45,46] and in contexts of social niche specialization [30]. Other feedback loops involving the reciprocal behaviours of two or more individuals include effects of the aggressiveness of individual X on individual Y and vice versa [47], and personality-dependent, predator-prey behavioural response games [48].…”
mentioning
confidence: 99%
“…The l ijk was predicted in a series of four different models accounting for the same fixed effects as above, but considering different partitioning of phenotypic and genetic variance, as suggested by recent literature (Arango et al, 2005;Muir, 2005;Chen et al, 2008;Wilson et al, 2009Wilson et al, , 2011. Different models were as follows:…”
Section: Models and Analysismentioning
confidence: 99%